The Relationship Between Knowledge And Drug Compliance In Hypertension Patients - Kartiko Utomo, Endrat; Widiastuti, Agung; Nasrul Sani, Fakhrudin; Rahma Soleman, Sitti; Risky Ain, Risky; Che Azmi, Norhaida; Syafiq Darul Redzuan, Ilyas (LPPM Universitas Duta Bangsa Surakarta, 2024)
Hypertension is one of the most common causes of untimely death worldwide and can result in an increased risk of mortality if left untreated. The treatment of hypertension requires the implementation of long-term therapy, so that in an effort to manage its therapy requires adherence and compliance in carrying out treatment. Knowledge about hypertension is also very important to shape one's awareness and behavior. The purpose of this study was to determine the relationship between knowledge and compliance with taking medication in hypertensive patients. Observational research method with cross-sectional design using non-probability sampling technique with purposive sampling approach. The research instrument used the Hypertension Knowledge Level Scale (HK-LS) questionnaire and the Probabilistic Medication Adherence Scale (ProMAS). Data analysis using Pearson correlation test. The results showed that there was a significant relationship between knowledge and medication adherence (p=0.003; r=0.320). Knowledge and compliance are very important in the treatment of hypertension to produce long-term blood pressure control effects and prevention of various complications that can be caused.